A Bibliometric Analysis of Synchronous Computer-Mediated Communication in Language Learning Using VOSviewer and CitNetExplorer - Yukun Hou; Zhonggen Yu (MDPI AG, 2023)
Synchronous computer-mediated communication in the online language classroom has gained growing attention in the wake of the worldwide epidemic. Nevertheless, only a few researchers have studied it through bibliometric analyses. This study aimed to retrospect the previous development and figure out the role of intercultural competence, social presence, and corrective feedback in synchronous computer-mediated communication-based language learning. Both quantitative and qualitative methods were employed to analyze previous studies (n = 1292) by VOSviewer and CitNetExplorer. The findings revealed prolific authors, sources, organizations, and regions in tables, which indicated that scholars in this field were mainly located in the USA and China. With a rising research tendency, several heated topics were also presented with VOSviewer. The findings also signified that intercultural competence, social presence, and corrective feedback all played an important role in synchronous computer-mediated communication-based language learning and they were interdependent. Implications for future studies were also discussed.